Molecular Target Identification of Gossypol Against Cervical Cancer Based on Target Fishing Technology - Jinyan Li; Rayisa Asat; Wenying Li; Parwen Parhat; Yue Ma; Yinglan Ma; Min Li (Pharmaceutics)
Objectives: This study aims to investigate the impact of Gossypol on human cervical cancer cells and elucidate its mechanism of action to establish a foundation for further clinical investigations. Methods: Cell proliferation, migration, and invasion were evaluated through CCK−8, wound healing, and Transwell assays. Fe3O4-BP-Gossypol (Fe3O4@Gossypol) conjugates were synthesized by linking Fe3O4 with Gossypol using benzophenone crosslinking. Successful conjugation was confirmed through scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and ultraviolet–visible spectrophotometry (UV-Vis). Subsequent to co-incubation with HeLa cell lysates, Fe3O4@Gossypol complexes facilitated the magnetic enrichment and purification of target proteins, which were identified using high-resolution mass spectrometry (HR-MS). The identified targets underwent KEGG pathway and GO analyses, followed by molecular docking with Gossypol. HeLa cells were exposed to Gossypol at concentrations of 7.48, 14.96, and 29.92 μmol·L−1 for 48 h, and protein expression levels were quantified via Western blotting. Results: Gossypol notably suppressed cervical cancer cell proliferation, migration, and invasion. The integration of target fishing, network pharmacology, and molecular docking highlighted PIK3R2, MAPK1, and GRB2 as potential therapeutic targets. Western blot analysis revealed a dose-dependent reduction in PIK3R2, GRB2, and MAPK1 expression in Gossypol-treated groups compared to controls (p < 0.05). Conclusions: Gossypol may exhibit anti-cervical cancer effects by modulating the PI3K/AKT signaling pathway.